Synthetic BSA-conjugated disaccharide related to the Streptococcus pneumoniae serotype 3 capsular polysaccharide increases IL-17A Levels, γδ T cells, and B1 cells in mice - Akhmatova, Nelli K.; Kurbatova, Ekaterina A.; Zaytsev, Anton E.; Akhmatova, Elina A.; Yastrebova, Natalya E.; Sukhova, Elena V.; Yashunsky, Dmitriy V.; Tsvetkov, Yury E.; Nifantiev, Nikolay E. (Frontiers in Immunology, 2024)
The disaccharide (β-D-glucopyranosyluronic acid)-(1→4)-β-D-glucopyranoside represents a repeating unit of the capsular polysaccharide of Streptococcus pneumoniae serotype 3. A conjugate of the disaccharide with BSA (di-BSA conjugate) adjuvanted with aluminum hydroxide induced — in contrast to the non-adjuvanted conjugate — IgG1 antibody production and protected mice against S. pneumoniae serotype 3 infection after intraperitoneal prime-boost immunization. Adjuvanted and non-adjuvanted conjugates induced production of Th1 (IFNγ, TNFα); Th2 (IL-5, IL-13); Th17 (IL-17A), Th1/Th17 (IL-22), and Th2/Th17 cytokines (IL-21) after immunization. The concentration of cytokines in mice sera was higher in response to the adjuvanted conjugate, with the highest level of IL-17A production after the prime and boost immunizations. In contrast, the non-adjuvanted conjugate elicited only weak production of IL-17A, which gradually decreased after the second immunization. After boost immunization of mice with the adjuvanted di-BSA conjugate, there was a significant increase in the number of CD45+/CD19+ B cells, TCR+ γδ T cell, CD5+ В1 cells, and activated cells with MHC II+ expression in the spleens of the mice. IL-17A, TCR+ γδ T cells, and CD5+ В1 cells play a crucial role in preventing pneumococcal infection, but can also contribute to autoimmune diseases. Immunization with the adjuvanted and non-adjuvanted di-BSA conjugate did not elicit autoantibodies against double-stranded DNA targeting cell nuclei in mice. Thus, the molecular and cellular markers associated with antibody production and protective activity in response to immunization with the di-BSA conjugate adjuvanted with aluminum hydroxide are IL-17A, TCR+ γδ T cells, and CD5+ В1 cells against the background of increasing MHC II+ expression.